Os “evangélicos sem fronteiras”: história e religiosidade evangélica em Londrina (PR) - Edson Elias de Morais (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
This article examined how the peculiar process of evangelical religion occurred in Londrina and how this process reproduces the dynamics of the national religion in the specific historical context. From bibliographical, electronics, field and oral research, it was identified that the evangelical religious trajectory of Londrina took place in four phases: the first one is called “ecumenical”; the second, “institutional division”; the third, “new religiousness” and the fourth “borderless evangelical”. As a final result, we affirm that this contemporary phase has characteristics that can be extended to the national level, given that the doctrines no longer delimit a church from another and that the gospel style is present in most of them.